Analysis on effects of variability of solar and wind energy and reserve planning in Luzon (Philippine) grid - Lagrama, Alyssa; Orillaza, Jordan Rel C. (Quezon City College of Engineering, University of the Philippines Diliman, 2019)
Large penetration of Variable Renewable Energy (VRE) Resources such as Solar and Wind Energy has brought in additional reserve equipment to the grid. Considering VRE intermittency and variability, a systematic procedure to size reserve equipments is presented in this study. It identified fluctuations, VRE prediction errors and load forecast errors as sources of imbalances. Various methods for calculating fluctuations were employed, accommodating both positive and negative fluctuations. Net imbalances were matched as secondary and tertiary reserve requirements. These calculations were done on 10-min intervals, for three weather seasons in a tropical country, namely: (i) cool dry, (ii) hot dry, and (iii) rainy. The results of the study produce an estimate Secondary and Tertiary reserve requirements in terms of Imbalances and should contribute to the process of reserve sizing as specified in the Grid Code, as practiced by the System Operator, and will soon be procured via the Electricity Market.
Thesis (Master of Science in Energy Engineering)--University of the Philippines Diliman
Keywords: Fluctuations (Physics); Renewable energy sources; Imbalances; Prediction errors; Load forecast errors; Reserve sizing; Variable renewable energy (VRE).